2017
DOI: 10.1182/bloodadvances.2017004333
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic effects of decorin restored by unfractionated, low molecular weight, and nonanticoagulant heparins

Abstract: Key Points• UFH, LMWH, and NAC restored angiogenesis in decorin-reduced endothelial cells.• NAC treatment was similar to, or better than, UFH or LMWH at improving endothelial angiogenesis without increasing anticoagulant activity.Pregnancies affected by preeclampsia (PE) or fetal growth restriction (FGR) display increases in thrombin generation and reductions in angiogenesis and cell growth. There is significant interest in the potential for low molecular weight heparins (LMWHs) to reduce the recurrence of PE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Conditioned medium from first‐trimester placental villous explants treated with dalteparin also stimulated endothelial tube formation as compared to medium that was untreated . In direct support of the notion that LMWH may protect against pre‐eclampsia through non‐anticoagulant mechanisms, a recent study showed that a chemically modified, non‐anticoagulant derivative of heparin can reverse the antiangiogenic properties of decorin‐reduced endothelial cells similarly to dalteparin . Interestingly, in a rat mesentery angiogenesis assay, dalteparin significantly stimulated angiogenesis in an inversely dose‐dependent manner at therapeutically relevant levels, ranging from prophylactic to maximum clinically acceptable doses .…”
Section: Potential Non‐anticoagulant Mechanisms Of Heparin In Pre‐eclmentioning
confidence: 91%
“…Conditioned medium from first‐trimester placental villous explants treated with dalteparin also stimulated endothelial tube formation as compared to medium that was untreated . In direct support of the notion that LMWH may protect against pre‐eclampsia through non‐anticoagulant mechanisms, a recent study showed that a chemically modified, non‐anticoagulant derivative of heparin can reverse the antiangiogenic properties of decorin‐reduced endothelial cells similarly to dalteparin . Interestingly, in a rat mesentery angiogenesis assay, dalteparin significantly stimulated angiogenesis in an inversely dose‐dependent manner at therapeutically relevant levels, ranging from prophylactic to maximum clinically acceptable doses .…”
Section: Potential Non‐anticoagulant Mechanisms Of Heparin In Pre‐eclmentioning
confidence: 91%
“…One can also draw attention to the fact that the increase in thrombin potential is characteristic for the development of preeclampsia [49,50], and LMWH improves angiogenesis by lowering thrombin generation [51].…”
Section: Partmentioning
confidence: 99%